THE JOURNAL OF REGIONAL HISTORY V.9 No.1 Monuments of Local Chronicle Writing of the 16th Century and Service Class People in the Russian State: A Review of Russian Historiography - Il'ya S. Agafonov (Historia provinciae: журнал региональной истории)
The article is devoted to the problem of reflection in Russian historiography of the known information about the monuments of local chronicles of the 16th century written by the representatives of the service class from among the clerks and nobility. In modern historical science, no attempts have been made to provide an overview of the accumulated complex of information about the works the authors of which came from the secular environment as a separate phenomenon of the local book culture of the Russian state. The introduction of the monuments of historical writing that were created by the persons who worked without patronage and direct guidance of secular and church authorities into a broader context of historiography of the Late Middle Ages and Early Modern Times is of interest in connection with a possible change in the approach to sources as a reflection of the author’s view of the reality surrounding him. The article pays special attention to the established ideas of Russian historians about the origin, composition, and authorship of the Postnik and Bezdnin chronicles and the Chronicle of the Izvol'sky Nobles as works of local chronicle writing. In the course of the work, the author points out the achievements of M. Tikhomirov and N. Belov in the study of the texts and social connections of the authors of the Postnik Chronicle and the Chronicle of the Izvol'sky Nobles, respectively. Particular attention is paid to the discussion dedicated to the personality and political orientation of the Duma nobleman M. Bezdnin as well as the intended purpose of the chronicle that he created in the mid-1580s after retiring to a monastery. The review of the domestic historiography of noble and clerical chronicle writing in sixteenth-century Russia shows that the questions related to the authorial self-awareness of the creators of historical works and the principles of their work in connection with the selection of information for their creations remain on the periphery of research interests.